2022
DOI: 10.1155/2022/1896781
|View full text |Cite
|
Sign up to set email alerts
|

Rhubarb Enema Increasing Short-Chain Fatty Acids that Improves the Intestinal Barrier Disruption in CKD May Be Related to the Regulation of Gut Dysbiosis

Abstract: The incidence of CKD seriously endangers people’s health. Researchers have proposed that improving the intestinal barrier damage in CKD may be an effective target for delaying the progression of CKD. Rhubarb can effectively improve the intestinal barrier and renal fibrosis, which may be related to the regulation of gut dysbiosis, but the mechanism needs to be further studied. Short-chain fatty acids (SCFAs) are important metabolites of the gut microbiota and play an important role in maintaining the intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…SCFAs show many positive regulatory functions, including serving as a major energy source for colonocytes (Vaziri et al., 2016), immunomodulation (Koh et al., 2016), enhancing gut barrier integrity and function (G. Chen et al., 2018; Ramezani et al., 2016), promoting the production of gut hormones (Iwasaki et al., 2019), improving metabolic health (Morrison & Preston, 2016), and especially slowing the progression of CKD (H. Zhu et al., 2021). An experiment of 5/6 nephrectomy model rat experiment revealed that gut bacteria producing SCFAs could improve kidney pathology and regulate intestinal tight junction proteins (Ji et al., 2022). According to the recent studies, SCFAs demonstrated a protective role against acute tubular injury from inflammation (Corrêa‐Oliveira et al., 2016) by means of inhibiting HDAC and directly activating G‐coupled receptors (Koh et al., 2016), such as GPR41 and GPR43 (Barrows et al., 2015; Kobayashi et al., 2017).…”
Section: Plant‐derived Bioactive Ingredients and Ckdmentioning
confidence: 99%
“…SCFAs show many positive regulatory functions, including serving as a major energy source for colonocytes (Vaziri et al., 2016), immunomodulation (Koh et al., 2016), enhancing gut barrier integrity and function (G. Chen et al., 2018; Ramezani et al., 2016), promoting the production of gut hormones (Iwasaki et al., 2019), improving metabolic health (Morrison & Preston, 2016), and especially slowing the progression of CKD (H. Zhu et al., 2021). An experiment of 5/6 nephrectomy model rat experiment revealed that gut bacteria producing SCFAs could improve kidney pathology and regulate intestinal tight junction proteins (Ji et al., 2022). According to the recent studies, SCFAs demonstrated a protective role against acute tubular injury from inflammation (Corrêa‐Oliveira et al., 2016) by means of inhibiting HDAC and directly activating G‐coupled receptors (Koh et al., 2016), such as GPR41 and GPR43 (Barrows et al., 2015; Kobayashi et al., 2017).…”
Section: Plant‐derived Bioactive Ingredients and Ckdmentioning
confidence: 99%
“…argued that picroside II increases the abundance of Lactobacillus , Prevotella , and restores the intestinal barrier by inhibiting the TLR4-dependent PI3K/AKT/NF-κB pathway, which thereby alleviates SAP ( 11 ) ( 176 ). Moreover, emodin has been reported to repair intestinal barrier functions and alleviate PALI by upregulating SCFA-producing bacteria (such as Akkermansia Muciniphila and Bacteroides ) ( 177 ).…”
Section: Interventions By Regulating the Intestinal Microbiotamentioning
confidence: 99%
“…It may be related to the increase in the abundance of commensal organisms and the decrease in the abundance of conditionally pathogenic species. Another study by the same research team found that Rheum palmatum L. enema (0.2 g/ml×5 ml) increased the content of SCFAs in the intestine of 5/6 Nephrectomy rats by increasing the abundance of SCFA-producing flora such as Akkermansia-muciniphila , lactobacillus-acidophilus , Bacteroides-caccae , and Faecalibaculum-rodentium , thereby regulating tight junction proteins and repairing the damaged intestinal barrier, which reduced inflammation and improved kidney functions ( Ji et al, 2022 ). In the three studies described above, Rheum palmatum L. granules were used.…”
Section: Herbal Medicine Gut-kidney Axis and Dkd/ckdmentioning
confidence: 99%